EDUKASI PENCEGAHAN BURNOUT DALAM PELAYANAN GEREJAWI MELALUI SEMINAR “MELAYANI SAMBIL TERLUKA” - Yogi Mahendra; Susanna Kathryn; Donny Charles Chandra (Penerbit Widina, Widina Media Utama, 2026)
This community service program aimed to improve church ministers’ literacy and awareness regarding burnout prevention in ecclesial ministry through a seminar entitled “Serving While Wounded.” Burnout in church ministry is a serious issue because it is associated with emotional exhaustion, decreased motivation, spiritual fatigue, relational conflict, and reduced ministry effectiveness. The program employed an educational-participatory approach through a seminar, material presentation, interactive discussion, reflective sharing, and participant evaluation. The activity involved 113 participants, consisting of church ministers, ministry activists, theology students, small group leaders, and congregation members actively engaged in ministry. The results indicate an increase in participants’ understanding of the concept of burnout, its symptoms, risk factors, and prevention strategies. The participants’ average pre-test score of 56.8 increased to 85.5 in the post-test, reflecting an improvement of 28.7 points. In addition, participant responses showed positive results; most participants stated that the seminar material was relevant to their ministry experience, helped them understand the symptoms of burnout, and provided practical strategies for maintaining the mental and spiritual well-being of church ministers. Therefore, this seminar contributed to developing critical awareness that healthy church ministry requires not only dedication but also self-management, healthy ministry boundaries, community support, and sustainable spiritual renewal. ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan literasi dan kesadaran pelayan gereja mengenai pencegahan burnout dalam pelayanan gerejawi melalui seminar bertema “Melayani Sambil Terluka”. Burnout dalam pelayanan gereja merupakan persoalan serius karena berkaitan dengan kelelahan emosional, penurunan motivasi, kejenuhan spiritual, konflik relasional, serta menurunnya efektivitas pelayanan. Metode pelaksanaan kegiatan menggunakan pendekatan edukatif-partisipatif melalui seminar, penyampaian materi, diskusi interaktif, refleksi pengalaman, dan evaluasi peserta. Kegiatan ini diikuti oleh 113 peserta yang terdiri atas pelayan gereja/aktivis pelayanan, mahasiswa teologi, pemimpin kelompok kecil/komsel, dan jemaat aktif dalam pelayanan. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta mengenai konsep burnout, gejala, faktor risiko, dan strategi pencegahannya. Rata-rata nilai pre-test peserta sebesar 56,8 meningkat menjadi 85,5 pada post-test, dengan peningkatan sebesar 28,7 poin. Selain itu, respons peserta terhadap kegiatan menunjukkan hasil positif; mayoritas peserta menyatakan bahwa materi seminar relevan dengan pengalaman pelayanan, membantu memahami gejala burnout, serta memberikan strategi praktis dalam menjaga kesehatan mental dan spiritual pelayan. Dengan demikian, seminar ini berkontribusi dalam membangun kesadaran kritis bahwa pelayanan gerejawi yang sehat tidak hanya menuntut dedikasi, tetapi juga memerlukan pengelolaan diri, batas pelayanan yang sehat, dukungan komunitas, dan pemulihan spiritual yang berkelanjutan.